Photic sensitivity for circadian response to light varies with photoperiod - Glickman, Gena; Webb, Ian C; Elliott, Jeffrey A; Baltazar, Ricardo M; Reale, Meghan E; Lehman, Michael N; Gorman, Michael R (Journal of biological rhythms, 2012)
The response of the circadian system to light varies markedly depending on photic history. Under short day lengths, hamsters exhibit larger maximal light-induced phase shifts as compared with those under longer photoperiods. However, effects of photoperiod length on sensitivity to subsaturating light remain unknown. Here, Syrian hamsters were entrained to long or short photoperiods and subsequently exposed to a 15-min light pulse across a range of irradiances (0-68.03 µW/cm(2)) to phase shift activity rhythms. Phase advances exhibited a dose response, with increasing irradiances eliciting greater phase resetting in both conditions. Photic sensitivity, as measured by the half-saturation constant, was increased 40-fold in the short photoperiod condition. In addition, irradiances that generated similar phase advances under short and long days produced equivalent phase delays, and equal photon doses produced larger delays in the short photoperiod condition. Mechanistically, equivalent light exposure induced greater pERK, PER1, and cFOS immunoreactivity in the suprachiasmatic nuclei of animals under shorter days. Patterns of immunoreactivity in all 3 proteins were related to the size of the phase shift rather than the intensity of the photic stimulus, suggesting that photoperiod modulation of light sensitivity lies upstream of these events within the signal transduction cascade. This modulation of light sensitivity by photoperiod means that considerably less light is necessary to elicit a circadian response under the relatively shorter days of winter, extending upon the known seasonal changes in sensitivity of sensory systems. Further characterizing the mechanisms by which photoperiod alters photic response may provide a potent tool for optimizing light treatment for circadian and affective disorders in humans.